Ethnoscience Study of Wu’u as a Local Food Ingredient for the Ende District Community - Priska, Melania; Wae, Veronika Praja Sinta Mbia; Lidi, Maria Waldetrudis (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2024)
Ethnoscience studies play an important role as a source of knowledge because they are based on local wisdom and involve traditions that occur in everyday life according to the contextual conditions of the local community environment so that they can be applied and absorbed by the community. Local wisdom and traditions can be in the form of local food, one of which is Wu’u. Wu’u is a local food made from corn that has existed and been passed down from generation to generation by the ancestors of the Ende Regency community as an alternative food made during times of famine and as provisions because of its long-lasting nature. However, along with the development of the era, the traditional knowledge of the community about the processing of local Wu’u food is threatened with extinction due to the lack of information passed down from previous generations due to the development of the era. This study examines the scientific concept of processing local Wu’u food with an ethnoscience approach. The method used in this study is descriptive qualitative in the form of direct observation, interviews, and documentation, as well as literature studies from journals and other reference books. The results of the study indicate that the indigenous knowledge of the Ende district community related to the process of making Wu’u consists of several stages of processing which are then transformed into scientific knowledge, so that from these stages of processing Wu’u has the opportunity as a source of learning science. The concept of scientific knowledge contained in the local Wu’u food processing process includes concepts of physics, chemistry, biology, and technology.